Ответы и объяснения

  • Endy
  • новичок
2013-03-20T21:30:35+04:00
Лучший Ответ!
  • Yena
  • главный мозг
2013-03-20T21:37:38+04:00

\frac{x}{x-3}-\frac{5}{x+3}=\frac{18}{x^2-9}

ОДЗ    x-3\neq0         x+3\neq0

              x\neq3              x \neq-3

\frac{x(x+3)-5(x-3)}{(x-3)(x+3)}=\frac{18}{x^2-9}

\frac{x^2+3x-5x+15}{x^2-9}=\frac{18}{x^2-9}

x^2-2x+15=18

x²-2x-3=0

D=4+12=16

x_1=\frac{2+4}{2}=3 Не удовлетворяет ОДЗ

x_2=\frac{2-4}{2}=-1

........................................................................................................................................................................................................................................................................................................................................................